Intramyocardial Sprouting Tip Cells Specify Coronary Arterialization. - Cano-Rincón, Elena; Schwarzkopf, Jennifer; Kanda, Masatoshi; Lindberg, Eric; Hollfinger, Irene; Pogontke Díaz, Cristina; Braeuning, Caroline; Fischer, Cornelius; Hübner, Norbert; Gerhardt, Holger (American Heart Association, 2024)
The elaborate patterning of coronary arteries critically supports the high metabolic activity of the beating heart. How coronary endothelial cells coordinate hierarchical vascular remodeling and achieve arteriovenous specification remains largely unknown. Understanding the molecular and cellular cues that pattern coronary arteries is crucial to develop innovative therapeutic strategies that restore functional perfusion within the ischemic heart. Results: We discover that coronary arteries originate from cells that have previously transitioned through a specific tip cell phenotype. We identify nonoverlapping intramyocardial and subepicardial tip cell populations with differential gene expression profiles and regulatory pathways. Esm1-lineage tracing confirmed that intramyocardial tip cells selectively contribute to coronary arteries and endocardial tunnels, but not veins. Notably, prearterial cells are detected from development stages to adulthood, increasingly in response to ischemic injury, and in human embryos, suggesting that tip cell-to-artery specification is a conserved mechanism. Conclusions: A tip cell-to-artery specification mechanism drives arterialization of the intramyocardial plexus and endocardial tunnels throughout life and is reactivated upon ischemic injury. Differential sprouting programs govern the formation and specification of the venous and arterial coronary plexus.
Keywords: Arterias coronarias; Angiogenesis; Arteries; Coronary vessels; Endocardium